MODEL SIMULASI PENGOPERASIAN WADUK BILI-BILI UNTUK OPTIMASI KAPASITAS SUPLAI AIR IRIGASI DAN AIR BAKU DI DAERAH ALIRAN SUNGAI JENEBERANG PROPINSI SUL- SEL - , Mustaqim; , Ir. Adam Pamudji Rahardjo, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Symptoms of urban development in South Sulawesi has a trend to minimize the open green spaces and converted into shops, shopping centers, residential, hotel, recreational areas and industrial. While the potential water availability has decreased with the increasing population growth and industrial sectors. This study aims to know the potential water availability of Bili-Bili dam for water supply served by constructing reservoir operation pattern. Operation pattern Bili-Bili dam using simulation with Standard Operating Rule to get the best supply capacity and optimal release. The availability of water in the Jeneberang watershed were analyzed using model in HEC-HMS and Thomas- Fiering method to get the amount of water availability in future projections. Water demand calculated based on the standard from the Center for Irrigation Department of Public Works. The results showed on simulations with Standard Operating Rule, the optimal supply happens at the first planting schedule with target release scenario irrigated rice-rice-maize. At existing condition the irrigation water needs is 61,35 percent with target release of raw water 100 percent. On the 10-year and 20-year projections, the best results is 53.7 percent and 44.5 percent of irrigation water needs with target release raw water 100 percent.